Progress in preventing injuries: an online inventory of national policies. (1st March 2011) - Mitis, F; Sethi, D; Racioppi, F
Abstract : Introduction: As part of a 3-year collaborative project between WHO and the European Commission on progress achieved by Member States in implementing resolution EUR/RC55/R9 and the European Council Recommendation on the prevention of injuries, an inventory of national policies has been compiled by WHO Regional Office for Europe. Methods and results: A web-based database was created using national policies for injury and violence prevention using an internet search in English or German. This was supplemented with a questionnaire survey completed by health ministry focal persons for injury and violence prevention. 97 policies from 30 countries were uploaded on the internet in 2008. These have been supplemented further in 2009 when an additional 72 national policies were identified. A content analysis of policies is being carried out to identify factors thought to be conducive to policy development and implementation. The documents in the inventory reflect policy initiatives undertaken at national level by different sectors such as health, justice, interior, social affairs and transport. Information can be viewed and searched on a country basis or as part of a regional overview and can be searched by type of injury or violence, target group and lead sector. Conclusions: This inventory of national policies for injury and violence prevention is a resource for policy-makers and practitioners interested in seeking more information. It represents a user-friendly system that can be used as a baseline to map future progress, to advocate for greater commitment and action, and to facilitate the sharing of information.